Design and control of a three-DOF spherical tendon based manipulator - Gilbank, Kevin (University of Ottawa (Canada), 2005)
Within robotics, areas such as locomotion, unmanned aerial vehicles (UAV's), machine vision, and dexterity of robots intensive research has been performed. In considering the dexterity of robots, work has been done for various types of robots. Also the robotic ability to manipulate or closely mimic the agility of humans has been extensively investigated. Humans are able to do a wide variety of tasks based on the complex series of joints at the wrists. The area of research into robotic wrists has however never attempted to emulate the human wrist. The wrist with its tendons, ligaments, and metacarpals allow three degrees of freedom (DOF's), and this would be extremely advantageous in many scenarios where robots are used. The goal of this thesis was to emulate the human wrist, by conceiving and designing a 3 DOF manipulator which could be easily attached to any robot arm or similar device. The end result of this thesis was to design an easy to implement 3 DOF spherical tendon based manipulator, complete with control system for which the approximate systems response would be known. At the conclusion of the work this was indeed the end result, and all lessons learned are enclosed herein.
Keywords: Engineering, Mechanical.